RELEVANSI ISLAMISASI ILMU DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM KONTEMPORER - Aripin, Paisal; Oki Setiana Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of science and technology in the modern era has contributed significantly to educational development; however, it has also intensified the dichotomy between religious and secular sciences, resulting in a weakened integration of intellectual, moral, and spiritual dimensions within education. This condition highlights the importance of examining the concept of Islamization of knowledge as a paradigm for managing contemporary Islamic educational institutions. This study aims to analyze the relevance of the Islamization of knowledge in the management of Islamic educational institutions and its implications for the development of an integrative educational system. The research employed a qualitative approach using a library research method. Data were collected from primary and secondary sources, including books, scholarly journal articles, and relevant research findings, and were analyzed through content analysis techniques. The findings reveal that the Islamization of knowledge is highly relevant to the management of Islamic educational institutions through the integration of modern sciences with Islamic values in curriculum development, organizational culture, human resource management, and character building. Furthermore, it strengthens the identity of Islamic educational institutions while enhancing their ability to respond to globalization and technological advancements. The study concludes that the Islamization of knowledge serves as a strategic paradigm for developing Islamic education that is academically excellent, spiritually grounded, and responsive to contemporary challenges.